Autoimmune polyglandular syndrome type 1: a case report and brief review - Ifeanyi Nwosu; Oreoluwa Oladiran; Chinyere Ogbonna-Nwosu; Anulika Anyata (Journal of Community Hospital Internal Medicine Perspectives, 2019)
Autoimmune polyglandular syndrome (APS) type 1 is a rare autoimmune disorder inherited in an autosomal recessive pattern due to loss of function of the AIRE gene and defective removal of self-reactive T-lymphocytes during the process of thymic T cell maturation. Its manifestation starts early in life with the cardinal clinical disorders being one of muco-cutaneous candidiasis, Addison’s disease, and hypoparathyroidism. Recognizing the syndromic nature of one autoimmune disease will facilitate an active search for other conditions which would allow early detection, management, follow-up, and most importantly patient education and counselling to avoid potential complications. We present the case of a young immigrant with multiple endocrinopathies and mucocutaneous candidiasis who presented with features of adrenal insufficiency. Our aim was to briefly review APS type 1 as a disease entity and to highlight the importance of patient education in its management.